PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Hanavi, Moch Sukron; Handrito, Radityo Putro (Jurnal Kewirausahaan dan Inovasi, 2023)
Employee performance development and improvement is necessary for any companies in order to be able to maximally attain their business goals. Therefore, they carry out many ways to ensure the prime condition of their employee performance, including by identifying factors affecting it. It is currently believed that there are two factors that influence performance: work discipline and work motivation. Therefore, the objective of this study is to analyze (1) the direct effect of work discipline on employee performance, (2) the direct effect of work motivation on employee performance, and (3) the indirect effect of work discipline on employee performance. This research is considered as explanatory research, a study that aims to identify the relationships between two or more variables. The data of this research was harvested through a census conducted on all 100 employees of CV Sumber Berkah Sejahtera Pasuruan, a cigarette company. The analysis was conducted by applying multiple linear regression in SPSS (Statistical Product and Service Solutions). This study finds that (1) work discipline and work motivation significantly and simultaneously influence employee performance, (2) work discipline significantly and simultaneously affects employee performance, and (3) work motivation significantly and simultaneously influences employee performance.